The Role of Administrative Staff in Improving the Quality of Service in Schools - Alvaro, Rizky Rahmad; Triwiyanto, Teguh (Proceedings Series of Educational Studies, 2024)
This study discusses the role of administrative staff in improving the quality of service in schools. The main problem raised is the low efficiency and effectiveness of administrative services that can affect the overall learning process. The purpose of this study is to identify the contribution of administrative staff to improving the quality of service in the school environment. The method used is a literature study and qualitative analysis of data collected from various related studies. The results of the study indicate that administrative staff have an important role in maintaining the smooth running of the administrative process, such as managing student data, finances, and communication between schools and parents. In conclusion, competent and trained administrative staff are able to improve the quality of service in schools, thereby supporting the achievement of more optimal educational goals.